Pengaruh pengelolaan alokasi dana desa terhadap Peningkatkan kesejahteraan masyarakat - Mutia Sumarni (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2020)
This study aims to examine the effect of village fund management on improving the welfare of the community. The independent variable used in this study is village fund management. The dependent variable used in this study is welfare. This research uses quantitative research methods. The population in this study was the population of 2077 people, with the method of probability sampling with simple random sampling while the sample size was obtained from calculations using the Slovin formula with an error rate of 5% from 95 people. Sources of data in this study are primary data in the form of questionnaires. The data analysis technique used is simple linear regression analysis. Measurement of the questionnaire answered by respondents using a Likert scale using the Statistical Package for Social Sciences (SPSS). The results of this study indicate that the management of village funds to improve welfare has a positive effect. While the adjusted R2 value is 0.46 which shows the effect of the independent variable on the dependent variable that can be explained by the equation model is 46.0%, while the remaining 54.0% is explained by other variables not examined or outside the model. Keywords: Village fund management and welfare level